2003
DOI: 10.1007/pl00012558
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model for Deviations from the Cubic Law for a Fracture Undergoing Dilation or Closure

Abstract: Experimental observations show that flow through a fracture decreases more rapidly than the cube of the mean aperture (COOK, 1992). In order to provide a possible explanation of these experimental findings, we study creeping flow through a fracture of varying aperture that is symmetric about its midplane, using the power series of the stream function obtained by VAN DYKE (1987) for low Reynolds numbers. For the case of sinusoidally-varying walls, a simple expression relating the effective hydraulic aperture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 19 publications
5
73
0
Order By: Relevance
“…That approach requires the effects of tortuosity and variations in effective crack width arising from the irregular arrangement of contact points that bear the contact loads across the crack to be incorporated (e.g., Cappa & Rutqvist, 2011;Chivers, 2002;Dimadis et al, 2014;Elsworth & Goodman, 1986;Neuzil & Tracy, 1981;Pyrak-Nolte & Morris, 2000;Renshaw, 1995;Sisavath et al, 2003;Witherspoon et al, 1980;review by Zimmerman & Bodvarsson, 1996).…”
Section: Fluid Flow In a Crack And The Measurement Of Hydraulic Transmentioning
confidence: 99%
“…That approach requires the effects of tortuosity and variations in effective crack width arising from the irregular arrangement of contact points that bear the contact loads across the crack to be incorporated (e.g., Cappa & Rutqvist, 2011;Chivers, 2002;Dimadis et al, 2014;Elsworth & Goodman, 1986;Neuzil & Tracy, 1981;Pyrak-Nolte & Morris, 2000;Renshaw, 1995;Sisavath et al, 2003;Witherspoon et al, 1980;review by Zimmerman & Bodvarsson, 1996).…”
Section: Fluid Flow In a Crack And The Measurement Of Hydraulic Transmentioning
confidence: 99%
“…Table 1. The relative effect of incremental permeability increases for smooth and rough Poiseuille flow and for granularity percolation flow for empirics (I)-(III) [37][38][39].…”
Section: Crustal Deformation Energetics For Spatially-correlated Crusmentioning
confidence: 99%
“…If fracture surface roughness is included within the flow conduit, exponents for the effective Poiseuille flow factor ∆ m are modelled to increase from 3 to~5-10 [38,39]. The increased exponent heightens the effect of increments in defect population on fluid flow in tight rock.…”
Section: Flow Geometrymentioning
confidence: 99%
“…The derivation of the cubic law begins by assuming that the fracture walls can be represented by two smooth, parallel plates with infinite dimensions, separated by an aperture w. However, the real fractures have finite sizes, rough walls and variable apertures. It was shown that the parallel plate model is inadequate to describe the flow in natural fractures (Sisavath et al 2003).…”
Section: Fracture Permeability Coefficientmentioning
confidence: 99%